The Organization of Regional Clusters - Bell, Simon J.; Tracey, Paul; Heide, Jan B. (Academy of Management Review, 2009)
We introduce a model of interorganizational governance within regional clusters. Drawing on the “new institutional economics” literature, we show how firms' governance designs are shaped by the relationship between transaction-level characteristics and the cluster macroculture. We then consider how subsequent transaction-level governance designs are affected by path dependencies from past governance choices. Finally, we suggest that intertransactional path dependencies exhibit directional asymmetries, and we draw implications for the literature on clusters, on transaction costs, and on interorganizational relationships.